2018
DOI: 10.1007/s11033-018-4365-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human TRIM14 and its mutant form (P207L) promotes apoptosis in transgenic loaches

Abstract: The tripartite-motif (TRIM)14 protein, one of the TRIM family members, was shown to participate in the antiviral and antibacterial defence. Besides, it appears to play an essential role in the processes of oncogenesis. In some types of human tumour cells, TRIM14 has been shown to inhibit apoptosis, while in others-the overexpression of TRIM14 promotes apoptosis. However, whether TRIM14 mediates apoptosis in the normal cells remains unknown. In the present study, we investigated the possible participation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…In their work, Jia et al noted that to prevent excessive immune activation, mechanisms that suppress the TRIM14 expression, such as ring‐finger protein 125 (RNF125), are extremely important 31 . High levels of the TRIM14 expression were observed in connection with HIV and SIV infections 32 . In contrast to our results, a high expression level was also found in the case of influenza A, HCV, and rhinovirus infections 33‐35 .…”
Section: Discussioncontrasting
confidence: 93%
“…In their work, Jia et al noted that to prevent excessive immune activation, mechanisms that suppress the TRIM14 expression, such as ring‐finger protein 125 (RNF125), are extremely important 31 . High levels of the TRIM14 expression were observed in connection with HIV and SIV infections 32 . In contrast to our results, a high expression level was also found in the case of influenza A, HCV, and rhinovirus infections 33‐35 .…”
Section: Discussioncontrasting
confidence: 93%
“…It is exciting that these data were confirmed in H9C2 cardiomyocytes. The subcellular localization showed that TRIM protein family were located in cytosol and nucleus, and some TRIM proteins are capable to induce apoptosis, while the others, on the contrary, have an inhibitory effect on this process (Nenasheva and Stepanenko, 2018). TRIM69 regulated cell apoptosis through p53 signaling (Han et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM29 could bind to Tip60, and reduce acetylation of p53 at lysine 120 by Tip60, promoting cancer cell proliferation and enhancing transformation [ 165 ]. TRIM14 was reported to activate C-myc, p53, and Bax gene expression during embryonic development to modulate apoptosis [ 166 ]. TRIM32 [ 167 ].…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%